A New Configuration Diplexer for RF Harvesting Applications - Bakkali Ahmed; Zbitou Jamal; El Gibari Mohammed; Oukaira Aziz; Samira Khoulji (EPJ Web of Conferences)
This paper presents an advanced microstrip diplexer specifically engineered for radio frequency (RF) energy harvesting. As key elements in multi-band harvesting setups, diplexers allow for the concurrent capture and conversion of ambient RF power across several frequency bands, leading to a substantial increase in the total harvested energy. The proposed design incorporates two band-pass filters, tuned to 5.8 GHz and 2.26 GHz, and constructed on a 1.6 mm thick FR-4 substrate (with a dielectric constant of 4.4 and a loss tangent of 0.025). A thorough evaluation of the filters' architecture and performance confirms their capability to convert ambient RF energy effectively. The diplexer efficiently segregates these frequency bands, enabling independent processing and rectification of the captured energy at each frequency. Such separation is essential for achieving maximum energy harvesting efficiency by reducing interference between bands and allowing the implementation of optimized rectifier circuits tailored to each band. Simulated S-parameters corroborate crucial performance indicators, including excellent impedance matching (low S11), minimal insertion loss (high S21 and S31), and significant isolation between ports (low S23 and S32), all of which are paramount for successful RF energy harvesting.